N-linoleyltyrosine exerts neuroprotective effects in APP/PS1 transgenic mice via cannabinoid receptor-mediated autophagy - Chun-mei Long; Qi-xue Zheng; Yi Zhou; Yuan-ting Liu; Liu-ping Gong; Ying-chun Zeng; Sha Liu (Elsevier, 2021)
Anandamide (AEA) analogs show fair effects in counteracting the deterioration of Alzheimer's disease (AD). Our previous studies demonstrated that AEA analog-N-linoleyltyrosine (NITyr) exerted significant activities. In our current research, the role and mechanisms of NITyr were assessed in APP/PS1 mice mimicking the AD model. NITyr improved motor coordination in the rotarod test (RRT) and ameliorated spatial memory in the Morris water maze (MWM) but did not increase spontaneous locomotor activity in the open field test (OFT). In addition, NITyr protected neurons against β-amyloid (Aβ) injury via hematoxylin-eosin (HE) and Nissl staining. Moreover, the related biochemical indexes showed that NITyr reduced the levels of Aβ40 and Aβ42 in the hippocampus but did not affect the expression of p-APP and β-secretase 1 (BACE1). Furthermore, the autophagy inhibitor 3-methyladenine (3 MA) attenuated the effect of NITyr on animal behaviors and neurons. Meanwhile, NITyr upregulated the expression levels of LC3-II and Beclin-1, which were weakened by AM630 (an antagonist of CB2 receptor and a weak partial agonist of CB1 receptors). AM630 also weakened the role of NITyr in animal behaviors. Thus, NITyr improved behavioral impairment and neural loss by inducing autophagy mainly mediated by the CB2 receptor, and weakly mediated by the CB1 receptor.